2019
DOI: 10.1109/access.2019.2935759
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative Fraud Detection Model With Privacy-Preserving in Real CDR Datasets

Abstract: The researchers have shown broad concern about detection and recognition of fraudsters since telecommunication operators and the individual user are both suffering significant losses from fraud activities. Researchers have proposed various solutions to counter fraudulent activity. However, those methods may lose effectiveness in fraud detection because fraudsters always tend to cover their tracks by roaming among different telecommunication operators. What is more, due to the lack of real data, researchers hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“… Fraud Detection and Prevention: CDR data analysis is instrumental in detecting and preventing telecommunications fraud. By analyzing usage patterns and detecting anomalies in call behavior, operators can identify fraudulent activities such as call spoofing, SIM box fraud, and premium rate service fraud [ 4 ]. Customer Experience Management: CDR data analysis enables telecommunications operators to better understand customer behavior and preferences.…”
Section: Introductionmentioning
confidence: 99%
“… Fraud Detection and Prevention: CDR data analysis is instrumental in detecting and preventing telecommunications fraud. By analyzing usage patterns and detecting anomalies in call behavior, operators can identify fraudulent activities such as call spoofing, SIM box fraud, and premium rate service fraud [ 4 ]. Customer Experience Management: CDR data analysis enables telecommunications operators to better understand customer behavior and preferences.…”
Section: Introductionmentioning
confidence: 99%
“…AccordingtotheAmericanheritagedictionary,fraudistermedasthedeceptionthatisintentionally accomplishedinordertoperformtheunlawfulgain.However,frauddetectionisusedtoidentify thesymptomsoffraud.Someoftheexamplesthatincludefrauddetectionstrategiesareaccounting fraud, credit card fraud, and insurance fraud. However, the information collected from Nigeria Inter-bank settlement system (NIBSS) showed that the fraudulent transactions are at peak levels inthebankingsector.Inrecentdecades,thefraudsarebeingevolvedandcommittedfromcasual fraudstersintotheorganizedcrimesuchthatthefraudringsutilizedsomesophisticatedtechniques tocontrolthecommitandaccountsoffraud.AccordingtotheresearchofJavelinin2007,nearly 6.8millionAmericansareoffendedthroughcardfraud.In2007,thefraudsintheexistingaccounts faced$3billionloss.Moreover,theNilsonreportspecifiesthecostoftheindustryas$4.84billion (Makki,et al,2019;Nilson,2007;John,et al,2016).In2007,Javelinstatesthetransactionloss amountas%30.6billion (Kim,&Monathan,2008;John,et al,2016).In2006,cardfraudmakes thetransactionlossof423millionaccordingtotheUKeconomy.Moreover,creditcardfraudloses accounttransactionsof$600milliongloballyeachyear (John,et al,2016).Fraudisthecriminalor wrongfuldeceptionthatisintendedtobringthepersonalorthefinancialgain (Zanetti,et al,2017;John,et al,2016;Randhawa,et al,2018).Theresearchworksinfraudreductionarecategorizedinto twotopics(i)frauddetectionand(ii)fraudprevention.Fraudpreventionistheproactiveapproach, wherethecauseoffraudisstopped (Gowthami,et al,2018;Cristin,et al,2019).However,fraud detectionishighlyrequiredwhenfraudulenttransactionsareacceptedbythefraudster (Ruan,et al, 2019;Randhawa,et al,2018).…”
Section: Introductionmentioning
confidence: 99%